Peran Modal Sosial dalam Pengembangan UMKM di Kampung Tahu Kediri pada Masa Pandemi Covid-19 - Nesya Vashti Engracia; Elya Kurniawati; Nur Hadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The current pandemic which was caused by the COVID-19 has weakened Indonesia's economic conditions, which resulted in a decline in demand for businesses engaged in food and beverages. This encourages SMEs in Kampung Tahu Kediri (Kediri's Tofu Village) to utilize social capital in maintaining and developing their businesses. The purpose of this research is first to analyze the role of social capital in the development of new product innovations for SMEs in Kampung Tahu Kediri. Second, to analyze the role of social capital in building a network of SMEs Kampung Tahu Kediri. The data were collected through observation and interviews and analyzed qualitatively. The results are the following;  first, social capital plays an effective role in the development of new product innovations because every business owner has elements of resources, relationships, and networks. This product innovation can bring benefits for business actors. Second, social capital plays an effective role in building SME networks in Kampung Tahu Kediri because business actors can utilize elements of resources, relationships,  and networks. The network that is built can increase the existence of Kampung Tahu Kediri in various cities.